2000
DOI: 10.1097/00003226-200005000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Keratoplasty for Keratoconus

Abstract: This study reaffirms that the results for keratoplasty in keratoconus are very positive and emphasizes that ophthalmologists should counsel patients about the likelihood of the need for spectacle or contact lens correction. Our data demonstrate that the majority of patients require optical correction for functional visual acuity after keratoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
19

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 15 publications
6
51
0
19
Order By: Relevance
“…Sayegh et al (26) and Brierly et al (4) reported similar results. In the present study, 68.2% of patients achieved 20/40 or better following surgery, which compares favorably with rates of 47% to 91% reported in the literature.…”
Section: Discussionmentioning
confidence: 56%
“…Sayegh et al (26) and Brierly et al (4) reported similar results. In the present study, 68.2% of patients achieved 20/40 or better following surgery, which compares favorably with rates of 47% to 91% reported in the literature.…”
Section: Discussionmentioning
confidence: 56%
“…A amostra estudada constou de pacientes relativamente jovens, com média de idade de 29,5 ± 9,8 anos, e houve discreta predominância masculina de 58%, resultados semelhantes a estudos anteriores (1,4,9) . As incidências de rejeição do enxerto são geralmente baixas nos pacientes com ceratocone.…”
Section: Discussionunclassified
“…As incidências de rejeição do enxerto são geralmente baixas nos pacientes com ceratocone. A freqüência de rejeição do enxerto de 17,4% neste estudo é similar às freqüências relatadas em estudos anteriores, que variavam de 7,8 a 31% (1) . O glaucoma pós-operatório foi a complicação mais freqüentemente encontrada no presente estudo, acometendo 26,1% dos olhos operados, incidência compatível com a literatura, onde variou de 10% a 34,1% (2,4,9) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Keratokonusta santral ya da parasantral kornea stromasında progresif incelme ve korneanın öne doğru uzaması sonucunda kornea koni şeklini alır ve buna bağlı dü-zensiz astigmatisma ve refraktif miyopi gelişir. [3,4] Hastalık puberte döneminde başlar yavaş bir progresyon gösterir. Genellikle iki taraflı tutulum gösterir ancak hastalığın şiddeti gözler arasında farklılık gösterebilir.…”
Section: Introductionunclassified